SAT0409 The New ERA of Anti-Phospholipid Antibodies: from Immunoenzymatic to Chemiluminescence Methods. (9th June 2015) - Fabris, M.; Tanzi, N.; Giacomello, R.; Marangone, M.; Curcio, F.; Tonutti, E.
Abstract : Background: The laboratory arm of the diagnostic process of the anti-phospholipid antibodies (aPL) syndrome is facing a crucial moment of renewal thanks to the availability both of new serological biomarkers and of new analytical methods. Objectives: To compare the analytical performance of immunoenzymatic (ELISA) and chemiluminescence (CLIA) aPL tests during twelve months of observation. Methods: We collected data on aCL (anti-cardiolipin), aB2GPI (anti-B2-glycoprotein I) IgG and IgM antibodies of 2628 patients, referred to our diagnostic Laboratory from October 2013 to October 2014. From October 2013 to may 2014 anti-phospholipid (aPL) antibodies were analysed by ELISA (Orgentec, Idk; cut-off aCL IgG >10 U/ml, aCL IgM >8 U/ml, aB2GPI IgG/IgM >8 U/ml) while from june 2014 to October 2014 they were analysed by CLIA (Zenit RA, Menarini Diagnostics; cut-off IgG >20 U/ml, IgM >10 U/ml). Lupus anticoagulant (LAC) assays were done in all cases following standardized methods. Results: By ELISA we found 61/1625 (3.8%) aCL IgG+ patients, among which 36 (59%) were also aB2GPI IgG+, and 108/1625 (6.6%) aCL IgM+ patients, among which 89 (82.4%) also B2GPI IgM+. On the other hand, among the overall 57/1625 (3.5%) aB2GPI IgG+ patients, 36 (63.2%) were also aCL IgG+ and among the overall 106/1625 (6.5%) aB2GPI IgM+ patients, 89 (83.9%) were also aCL IgM+. However, when considering aB2GPI IgG or IgM >40 U/ml, 100% of positive aB2GPI samples were also aCL positive. By CLIA, we found 38/1003 (3.8%) aCL IgG+ patients, among which 37 (97.4%) also aB2GPI IgG+ and 125/1003 (12.5%) aCL IgM+ patients, among which 100% were also aB2GPI IgM+. Furthermore, among the overall 42/1003 (4.2%) aB2GPI IgG+ patients, 40 (95.2%) were also aCL IgG+, while among the overall 163/1003 (16.3%) aB2GPI IgM+ patients, 127 (77.9%) were also aCL IgM+. Again, when considering only high IgG+ or IgM+ aB2GPI titres (>40 U/ml) all samples were also aCL IgG+ or IgM+. The percentage of aB2GPI IgG+ and/or IgM+ positive cases within the LAC positive patients increased from 43/154 (27.9%) by ELISA to 42/92 (45.7%) by CLIA (p=0.0056; 95%CI: 1.26-3.72, OR 2.17). Conclusions: The CLIA method showed comparable sensitivity to ELISA for high titres samples, while improved significantly the overall aB2GPI specificity of the aCL tests and, more importantly, the correlation with LAC activity. Low positive aB2GPI IgM samples increased, probably due to the intrinsic high sensitivity of the CLIA method, suggesting a possible reformulation of the cut-off. Disclosure of Interest: None declared